PORTOFOLIO SAHAM OPTIMAL MENGGUNAKAN SINGLE INDEX MODEL PADA SELURUH KANTOR SEKURITAS DI KOTA MALANG - Anthony Satyanegara; Tarsisius Renald Suganda (Jurnal Keuangan dan Perbankan, 2012)
Investment was the commitment of funds to one or more assets that would be held over some future time period.The goal of doing investment was to get the best return. Investment portfolio was one of the main considerationsto achieve the goal. This study aimed to establish the optimal stock portfolio using stock mutual fund productdata which was obtained from the survey results on securities office in Malang City in 2011 as a researchpopulation. Research method used was Single Index Model and data used were daily stock prices for 47 sharesin 2011. The results of this study indicated that there were twelve stocks in the optimal portfolio, namely:JKON, KAEF, TSPC, BKSL, BFIN, MAPI, KKGI, BHIT, CTRA, GGRM, MYOR. Based on the calculation, theresult was 76.71% for portfolio expected return and 7.23% for portfolio risk in 1 year.